A RE-EVALUATION OF THE GENUS TROPIDOSTOMA SEELEY - Keyser, A. W. (BERNARD PRICE INSTITUTE FOR PALAEONTOLOGICAL RESEARCH, 1973)
The type specimens of Cteniosaurus platyceps Broom, Dicynodon acutirostris Broom, and Dicynodon validus Broom were re-examined and were found to be very similar in a number of features rarely encountered in other Anomodontia. The skull of the type of Cteniosaurus platyceps is described in some detail. It is concluded that the above species must be considered to be junior synonyms of Tropidostoma microtrema (Seeley).